Unsystematic drug use in hypertension treatment as a life and health threatening problem - Izabela Kamila Wojarska; Ewelina Nowak; Dominika Materek (Kazimierz Wielki University, 2017)
Hypertension remains the most important risk factor for premature death, not only in Poland but worldwide. The Natpol research conducted in 2011 shows that 32% of adult Poles suffers from hypertension. About 9% of the hypertensive patients doesn't start treatment despite of the diagnosis, and the treatment is inefficient in 36% of cases. The cardiovascular system diseases like heart attack, stroke, heart failure or the peripheral artery disease are significantly dependent on the blood pressure level. Lowering the blood pressure of every mm Hg reduces the risk of serious cardiovascular events in the group of younger patients and older patients. The effective treatment of hypertension is still a big challenge due to the nature of this disease and the long term treatment process. The treatment of hypertension is problematic since patients forget about taking medication, take the particular doses with delay or completely stop using the prescribed medication. The treatment termination usually leads to a blood pressure rise to the same level as before treatment. The key issue is stressing the importance of suiting the medication to the patients individual needs. The purpose is that the patient feels the least side effects with the best possible therapeutic effect.